Calcium fertilizers induce soil suppressiveness to Phytophthora cinnamomi root rot of Quercus ilex - Serrano, María Socorro; Vita, Paolo; Fernández-Rebollo, Pilar; Sánchez Hernández, María Esperanza (European Journal of Plant Pathology, 2011)
t Based on the observation that the root disease caused by P. cinnamomi on Q. ilex has a low incidence and severity in soils with medium-high Ca 2+ content, we studied the ability of Ca 2+ fertilizers to induce soil suppressiveness to the pathogen. Studies on cultures of P. cinnamomi exposed to different Ca 2+ fertilizers in vitro showed significant inhibition of sporangial, chlamydospore and zoospore production at millimolar concentrations while mycelial growth was mainly unaffected. Experiments performed with artificially infested soil showed that some Ca 2+ fertilizers induce a significant decrease on chlamydospore viability. Additionally, greenhouse experiments using artificially infested soils showed a significant reduction of foliar and root symptom severities in Holm oak seedlings growing in soils amended with Ca 2+ fertilizers. We suggest that limestone amendments in oak rangelands could enhance the suppressiveness of soils to P. cinnamomi, and it is likely that the inhibition of sporangial production was the main mechanism involved.
Keywords: fertilization; limestone; Oak decline; Rangelands

Incidence des caractéristiques structurales du sous-sol sur l'entrée en production de Tuber melanosporum et d'autres champignons mycorhiziens - Callot, G.; Jaillard, B.; Braye, J. P.; Jalade, M. (Agronomie, 1996)
Effect of structural characteristics of subsoil on the fruiting of Tuber melanosporum and other mycorrhizal fungi. The collection sites for ascocarps of Tuber melanosporum Vitt were noted over four consecutive years in a truffle bed of live oaks (Quercus ilex) mycorrhized by T melanosporum. The mycorrhizas of Tuber and other fungi were checked 11 years after planting. At the same time, a detailed soil survey made it possible to distinguish different soil units within the truffle bed. Cartographic analysis of the data set showed that the mycorrhizal status and the location of the fungus collection sites were related to the structural characteristics of the subsoil. The presence of a slightly permeable clay subsoil discourages fruiting in both epigeal and hypogeal fungi. Soils presenting a shallow calcareous crust discourage the growth of hypogeal Tuber-type fungi, but encourage that of epigeal fungi. T melanosporum grows best in soils with a very porous horizon developed in contact with the calcareous bedrock. This horizon (termed Bbio by the authors) is characterized by an intensive biological activity.
Keywords: autoecology; fungi; limestone; Mycorrhizas; subsoil; Tuber

Incidence des caractéristiques structurales du sous-sol sur l'entrée en production de Tuber melanosporum et d'autres champignons mycorhiziens - Callot, G; Jaillard, B; Braye, J P; Jalade, M (Agronomie, 1996)
Effect of structural characteristics of subsoil on the fruiting of Tuber melanosporum and other mycorrhizal fungi. The collection sites for ascocarps of Tuber melanosporum Vitt were noted over four consecutive years in a truffle bed of live oaks (Quercus ilex) mycorrhized by T melanosporum. The mycorrhizas of Tuber and other fungi were checked 11 years after planting. At the same time, a detailed soil survey made it possible to distinguish different soil units within the truffle bed. Cartographic analysis of the data set showed that the mycorrhizal status and the location of the fungus collection sites were related to the structural characteristics of the subsoil. The presence of a slightly permeable clay subsoil discourages fruiting in both epigeal and hypogeal fungi. Soils presenting a shallow calcareous crust discourage the growth of hypogeal Tuber-type fungi, but encourage that of epigeal fungi. T melanosporum grows best in soils with a very porous horizon developed in contact with the calcareous bedrock. This horizon (termed Bbio by the authors) is characterized by an intensive biological activity.
Keywords: autoecology; fungi; limestone; Mycorrhizas; subsoil; Tuber